Analisis Problematika pada Keterampilan Menulis Permulaan Siswa Kelas II Sekolah Dasar - Hidayati, Anisa; Fitriani, Desnita; Aprilia, Rara Nasywa; Fauziah, Sobrini (Lembaga Yasin AlSys, 2023)
Early writing skills are a critical aspect in a child's language development. This article provides an overview of early writing skills and identifies several challenges often encountered in developing writing abilities among children. The importance of early writing skills as the foundation for language learning and communication is the main focus. This stage involves introducing letter forms, fine motor training, and the ability to connect simple letters into meaningful words. Proficient writing skills serve as the basis for more complex language abilities in the future. However, there are several challenges faced in developing early writing skills in children. One of them is the lack of attention from parents and educators regarding the importance of these writing skills. Insufficient support and appropriate stimulation during the initial learning stage can hinder a child's writing development. Additionally, another challenge is the difficulty experienced by some children in overcoming fine motor obstacles. Their untrained hand-eye coordination makes it challenging to form letters clearly and neatly.